The Role of Ribonucleases and sRNAs in the Virulence of Foodborne Pathogens - Matos, Rute G.; Casinhas, Jorge; Bárria, Cátia; dos Santos, Ricardo F.; Silva, Inês J.; Arraiano, Cecília M. (Frontiers in Microbiology, 2017)
Contaminated food is the source of many severe infections in humans. Recent advances in food science have discovered new foodborne pathogens and progressed in characterizing their biology, life cycle and infection processes. All this knowledge has been contributing to prevent food contamination, and to develop new therapeutics to treat the infections caused by these pathogens. RNA metabolism is a crucial biological process and has an enormous potential to offer new strategies to fight foodborne pathogens. In this review, we will summarize what is known about the role of bacterial ribonucleases and sRNAs in the virulence of several foodborne pathogens and how can we use that knowledge to prevent infection.